A PHARMACOECONOMIC EVALUATION OF DRUGS IN PATIENTS OF PAINFUL DIABETIC NEUROPATHY - SINGH, JASPINDER PRATAP; SHARMA, AASHISH; Sharma, Chetna (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To study the effect of methylcobalamin, the combination of methylcobalamin with pregabalin, and methylcobalamin with duloxetine in patients with painful diabetic neuropathy after comparing the safety, tolerability, and economic implications of all three study groups. Methods: The present study was a prospective, open-labeled, interventional, randomized, and parallel-group study conducted on 100 patients of painful diabetic nephropathy from the outpatient department of the hospital who were recruited after obtaining informed consent. The permission for the study was taken from the Institutional Ethical Committee. The patients were randomized into three study groups: A, B, and C, on methylcobalamin, methylcobalamin, pregabalin, methylcobalamin, and duloxetine. Results: The mean value of the price of each tablet from all the brands of the respective drugs and finally calculating the cost for the whole 3 months which comes out to be Rs. 797.4 for group A, Rs. 1940.4 for group B, and Rs. 1163.7 for group C. The cost of the entire treatment and the effect produced in terms of the difference in the visual analog scale score from day 1 to the end of week 12 which are 0.58 for group A, 3.82 for group b, and 4.17 for group C. Conclusion: The primary purpose of the pharmacoeconomic evaluation is not to directly alter the therapeutic decisions of the physicians but to help the physicians, pharmacists, and policymakers to make informed decisions about whether the cost and extra benefits of the new drug are meaningful within the given budget.